Development and Characterization of Azadirachta indica-Mediated Gold Nanoparticle Carbopol Gel for Enhanced Antifungal Activity Against Candida albicans. - Kamble, Suraj; Chakole, Rita (Journal of Neonatal Surgery, 2025)
Background: Candida albicans is a major opportunistic fungal pathogen associated with superficial and systemic infections. The increasing incidence of antifungal resistance and limitations of conventional antifungal agents have prompted the development of plant-based nanotherapeutic systems with improved efficacy and safety. Objective: This study aimed to develop and characterize an Azadirachta indica (Neem)-mediated gold nanoparticle (AuNP)-loaded Carbopol gel and evaluate its antifungal activity against Candida albicans. Methods: Neem leaf extracts prepared using different solvents were screened for antifungal activity using the agar well diffusion method. The ethyl acetate extract, which exhibited the highest antifungal activity, was selected for green synthesis of AuNPs. The synthesized nanoparticles were characterized by UV-Visible spectroscopy, dynamic light scattering, zeta potential analysis, X-ray diffraction, and differential scanning calorimetry. AuNPs were incorporated into Carbopol gel and evaluated for physicochemical properties, in vitro drug release, and antifungal activity. Results: The ethyl acetate extract demonstrated the highest antifungal activity with inhibition zones of 12 and 19 mm at 5 and 10 mg/mL, respectively. The synthesized AuNPs exhibited a characteristic SPR peak at 559 nm, a mean particle size of 104.4 nm, a polydispersity index of 0.405, and zeta potential of −20.2 mV. The nanoparticles showed significant antifungal activity with an inhibition zone of 18 mm at 1 mg/mL. The optimized AuNP-loaded gel (GN2) exhibited a pH of 6.89, sustained drug release of 89.7% within 180 min, and enhanced antifungal activity with a 20 mm inhibition zone. Conclusion: The developed Azadirachta indica-mediated AuNP-loaded Carbopol gel represents a promising topical nanotherapeutic system for the effective management of candidal infections..